Returning Indonesian fighters from Syria and Iraq : learning from the past - Navhat Nuraniyah (2015)
Indonesian fighters with the self-declared Islamic State (IS) recently posted a video threatening to bring the armed struggle home. Indonesia can learn a lot from past handling of former foreign fighters who returned from the Afghan and Mindanao battlefronts.